Changes in the treatment responses to artesunate-mefloquine on the northwestern border of Thailand during 13 years of continuous deployment - Verena Ilona Carrara (2018)
Background: Artemisinin combination treatments (ACT) are recommended as first line treatment for falciparum malaria throughout the malaria affected world. We reviewed the efficacy of a 3-day regimen of mefloquine and artesunate regimen (MAS3), over a 13 year period of continuous deployment as first-line treatment in camps for displaced persons and in clinics for migrant population along the Thai-Myanmar border. Methods and Findings: 3,264 patients were enrolled in prospective treatment trials between 1995 and 2007 and treated with MAS3. The proportion of patients with parasitaemia persisting on day-2 increased significantly from 4.5% before 2001 to 21.9% since 2002 (p<0.001). Delayed parasite clearance was associated with increased risk of developing gametocytaemia (AOR = 2.29; 95% CI, 2.00-2.69, p = 0.002). Gametocytaemia on admission and carriage also increased over the years (p = 0.001, test for trend, for both). MAS3efficacy has declined slightly but significantly (Hazards ratio 1.13; 95% CI, 1.07-1.19, p<0.001), although efficacy in 2007 remained well within acceptable limits: 96.5% (95% CI, 91.0-98.7). The in vitro susceptibility of P. falciparum to artesunate increased significantly until 2002, but thereafter declined to levels close to those of 13 years ago (geometric mean in 2007: 4.2 nM/l; 95% CI, 3.2-5.5). The proportion of infections caused by parasites with increased pfmdr1 copy number rose from 30% (12/ 40) in 1996 to 53% (24/45) in 2006 (p = 0.012, test for trend). Conclusion: Artesunate-mefloquine remains a highly efficacious antimalarial treatment in this area despite 13 years of widespread intense deployment, but there is evidence of a modest increase in resistance. Of particular concern is the slowing of parasitological response to artesunate and the associated increase in gametocyte carriage. © 2009 Carrara et al.